2011
DOI: 10.1038/jp.2011.154
|View full text |Cite
|
Sign up to set email alerts
|

Causes of community stillbirths and early neonatal deaths in low-income countries using verbal autopsy: an International, Multicenter Study

Abstract: Objective Six million stillbirths (SB) and early neonatal deaths (END) occur annually worldwide, mostly in rural settings distant from health facilities. We used verbal autopsy (VA), to understand causes of non-hospital, community-based SB and END from four low-income countries. Study Design This prospective observational study utilized the train-the-trainer method. VA interviewers conducted standardized interviews; in each country data were reviewed by two local physicians who assigned an underlying causes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
32
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 42 publications
9
32
0
1
Order By: Relevance
“…[1][2][3] Despite these figures, perinatal health policies remain largely absent from global and national health agendas. 4,5 Over 99% of perinatal deaths occur in low-and middle-income countries and regional estimates suggest that west Africa has among the highest perinatal mortality rates in the world. 6,7 Additionally, many west African countries with high perinatal mortality rates have weak vital registration and health systems, resulting in poor quality perinatal morbidity and mortality data.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Despite these figures, perinatal health policies remain largely absent from global and national health agendas. 4,5 Over 99% of perinatal deaths occur in low-and middle-income countries and regional estimates suggest that west Africa has among the highest perinatal mortality rates in the world. 6,7 Additionally, many west African countries with high perinatal mortality rates have weak vital registration and health systems, resulting in poor quality perinatal morbidity and mortality data.…”
Section: Introductionmentioning
confidence: 99%
“…7 A study conducted on four low and middle income countries revealed a stillbirth rate of 30/1000 deliveries. 8 …”
mentioning
confidence: 99%
“…This may come from an inability to investigate in great detail the cause of perinatal death, particularly but not exclusively in the settings where most of the deaths occur. 12,13 With the challenges of classifying perinatal death, 7 it is even more critical that maximal information is extracted from the classification of the maternal condition at the time of perinatal death. Assigning the underlying cause of death from the perinatal point of view can be challenging, given that many settings lack resources to fully investigate the cause of death and there is a lack of clarity around when to assign a particular cause of death.…”
Section: Discussionmentioning
confidence: 99%